Assessment of pattern and outcomes of pesticides poisoning in a tertiary care hospital. Issue 12 (23rd October 2018) - Prashar, A.; Ramesh, M.
Summary: Objectives: To assess the socio‐demographic profile, pattern and treatment outcomes of pesticides poisoning. Methods: A prospective observational study was conducted at the department of emergency medicine of a South Indian tertiary care hospital for 1.5 years to study the pattern and outcomes of poisoning cases due to pesticides. Level of significance ( P ) <0.05 was considered as statistically significant. Results: A total of 375 poisoning victims with intentional/accidental exposure to pesticides were followed up and documented. The male–female ratio was 1:0.32; mean age was 31.65 ± 13.10 years. 72% of cases were rural residents. Organophosphorus compounds were the most implicated pesticides. Mean Glasgow Comatose Score (GCS) of the patients was 12.22 ± 3.86. 80.3% of patients recovered while 6.4% died. About 13.3% patients were lost to follow‐up as they were discharged against medical advice (DAMA). Conclusion: There was a statistical significance seen in the implication of pesticides for intentional poisoning with age, route of administration, area of residence and occupation of the victims. However, there was a strong association of the outcomes of poisoning with the toxic agent implicated for the poisoning.